Aflatoxins and fumonisins in feed from a broiler operation system from São Paulo state, Brazil - Kobashigawa,Estela (2019)
ABSTRACT: The aim of the present study was to assess the occurrence of aflatoxins (AFs) and fumonisins (FBs) in feed ingredients (corn and soybean meal) and finishing feed in a broiler operation system, as well was to evaluate their effect on the productivity of 20 batches of broilers produced and the histology status of broilers’ liver after slaughter. Corn samples presented the highest frequencies of AFs and FBs, at mean levels of 29.1 and 2,100µg/kg, respectively. Soybean samples presented mean levels of 1.5 and 70µg/kg for AFs and FBs, respectively. Batches of broilers receiving feed containing FB levels higher than 1,000µg/kg had lower weight gain and higher mortality rates, while those fed rations with AFs equal or above the limit of quantification (LOQ) of the analytical method presented higher scores of histological changes in the liver. A dilution effect was observed for AFs and FBs from ingredients, especially corn, to feed during manufacture, whilst not enough to prevent losses in productivity. Results of this trial highlighted the need for strict control of mycotoxins in corn intended for broilers.